2015
DOI: 10.1186/s12985-015-0401-6
|View full text |Cite
|
Sign up to set email alerts
|

First identification of porcine parvovirus 6 in North America by viral metagenomic sequencing of serum from pigs infected with porcine reproductive and respiratory syndrome virus

Abstract: BackgroundCurrently, eight species in four genera of parvovirus have been described that infect swine. These include ungulate protoparvovirus 1 (classical porcine parvovirus, PPV), ungulate tetraparvovirus 2 (PPV3), ungulate tetraparvovirus 3 (which includes PPV2, porcine hokovirus, porcine partetravirus and porcine PARV4), ungulate copiparvovirus 2 (which includes PPV4 and PPV5), ungulate bocaparvovirus 2 (which includes porcine bocavirus 1, 2 and 6), ungulate bocaparvovirus 3 (porcine bocavirus 5), ungulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 16 publications
1
53
3
1
Order By: Relevance
“…In the following year, Ni et al (2014) for the first time identified another novel pig parvovirus, tentatively named as PPV6, from aborted swine foetuses which showed negative results for other swine's reproductive failure pathogens in pigs in China. Subsequently, the virus has been detected through a high throughput sequencing of PRRSV positive serum samples from swine in the USA and Mexico, with a very high similarity to the PPV6 discovered in China (Schirtzinger et al, 2015). Reports from the two investigations have unanimously proposed the classification of the novel PPV6 under the genus Copiparvovirus alongside the PPVs 4 and 5, as they all formed the same cluster in their phylogenetic analyses and as it could be seen in Fig.…”
Section: Novel Unassigned Porcine Parvovirusesmentioning
confidence: 86%
See 2 more Smart Citations
“…In the following year, Ni et al (2014) for the first time identified another novel pig parvovirus, tentatively named as PPV6, from aborted swine foetuses which showed negative results for other swine's reproductive failure pathogens in pigs in China. Subsequently, the virus has been detected through a high throughput sequencing of PRRSV positive serum samples from swine in the USA and Mexico, with a very high similarity to the PPV6 discovered in China (Schirtzinger et al, 2015). Reports from the two investigations have unanimously proposed the classification of the novel PPV6 under the genus Copiparvovirus alongside the PPVs 4 and 5, as they all formed the same cluster in their phylogenetic analyses and as it could be seen in Fig.…”
Section: Novel Unassigned Porcine Parvovirusesmentioning
confidence: 86%
“…More recent ones are yet to be assigned into species and genus under the subfamily. These include PPVs 5, 6 and 7 (Xiao et al, 2013a;Ni et al, 2014;Schirtzinger et al, 2015;Palinski et al, 2016;Xing et al, 2018).…”
Section: The Observable Increase In the Number Of Porcine Parvovirusementioning
confidence: 99%
See 1 more Smart Citation
“…Again, we detected PPV6-related sequences in pigs that were slaughtered even in 1998 (and in a period spanning 1998–2004), more than 10 years before this virus was first recognized in China from specimens collected in 2010–2013 [32] and then identified in the United States and Mexico [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Human parvoviruses are known to be intransigent to in vitro culture and only a few have been propagated in cell culture such as the B19V and HBoV . In pigs, eight species of the Parvoviridae family classified under four genera are described (Table ); ungulate protoparvovirus 1 [classical porcine parvovirus (PPV) or PPV1], ungulate tetraparvovirus 2 (PPV3), ungulate tetraparvovirus 3 (PPV2, also known as porcine hokovirus or porcine partetravirus or porcine PARV4), ungulate copiparvovirus 2 (PPV4, PPV5 and PPV6), ungulate bocaparvovirus 2 [porcine bocavirus (PBoV) 1, 2 and 6], ungulate bocaparvovirus 3 (PBoV 5), ungulate bocaparvovirus 4 (PBoV 7), and ungulate bocaparvovirus 5 (PBoV 3, PBoV4.1 and PBoV4.2) . PPV1 was first identified in the early 1970s in association with abortions in pigs .…”
Section: Single‐stranded Dna Viruses In Pigsmentioning
confidence: 99%